A 9000-Year Old Wapiti (Cervus elaphus) Skeleton from Northern Alberta, and its Implications for the Early Holocene Environment - Burns, James (Géographie physique et Quaternaire, 1986)
ABSTRACTA complete and fully articulated adult male wapiti (Cervus elaphus) skeleton was recovered from the 50 m terrace of Smoky River, near Watino, Alberta. A collagen-based date on antler gave an age of 9075 ± 305 yr BP (S-2614). The local terrace sequence features three benches, and two previously described fossil sites are placed within it. The importance of the find is that it indicates an environment at 9000 yr BP similar to the present. A brief review of local deglaciation precedes discussion of the paleontology.